Mental Health for Hispanic Communities A Guide for Practitioners - Castilla-Puentes, Ruby.; Falcone, Tatiana; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book is the first authoritative medical text that considers the unique cultural backgrounds of Hispanic populations in a straightforward yet sensitive way, all while building a framework for practical psychiatric assessment and treatment plans. As the only book to consider the unique challenges facing Hispanic mental healthcare, this book is at the forefront of a serious issue that has gone unchallenged for too long. The text is written by two expert psychiatrists with an established history of leadership in this space. Chapters carefully and meticulously establish the issues of access to care in Latinx communities before addressing the unique needs of these patients in the context of common psychiatric disorders. Each disorder includes clinical cases for a reader-friendly approach to the challenges that develop effective assessment and treatment plans. Mental Health for Hispanic Communities is a concise yet comprehensive reference invaluable to all clinicians, students, and other medical professionals seeking to work with this population effectively. .
1. The role of religion in mental health -- 2. The role of history in mental health -- 3. Understanding the Stigma in Mental health -- 4. Psychosis -- 5. Mood Disorders -- 6. Anxiety Disorders -- 7. The role of acculturation -- 8. Eating Disorders -- 9. Substance abuse disorders -- 10. Geriatric Population -- 11. Children and Adolescents -- 12. Mental Health Services for Latino Populations -- 13. Treatment- Metabolic Factors.-14. Artificial Intelligence and Access to Treatment in Latinos/Hispanics.
Keywords: Psychiatry; Clinical psychology; Family medicine; Biotechnology; Public health; Psychiatry; Clinical Psychology; General Practice and Family Medicine; Biotechnology; Public Health; Hispanic or Latino; Mental Health Services; Mental Health -- ethnology; Cultural Characteristics; Population Groups, US; Psychiatry